Second Five-Year Plan Andhra Pradesh Review of Progress 1957-58 - Planning Commission (Planning Commission, 1957)
The outlay during the Second Year of the Second Plan was originally fixed at Rs. 3399.556 lakhs — Rs. 2333.861 lakhs in respect of Andhra Region and Rs. 1065.695 lakhs in respect of Telangana region. During the course of the year, certain changes were made in, the programme excluding some schemes from the programme, and bringing in certain additional schemes. Also, the original Plan provision for Nagarjunasagar Project vis., Rs. 550.00 lakhs was increased to Rs. 745.00 lakhs. These changes were necessitated on account of the revisions suggested by the Central Ministries in respect of provisions for certain schemes for which central assistance was available and also due to other administrative considerations involved in the implementation of schemes.
Planning and Development Department, Government of Andhra Pradesh